2002
DOI: 10.1097/00043764-200207000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Comorbidity and Outcome in Episodes of Nonspecific Low Back Pain in Occupational Populations

Abstract: We examined the relationship between comorbidity and first return to work after episodes of work-disabling, nonspecific low back pain (NSLBP). An inception cohort of workers with new episodes of NSLBP was identified from administratively maintained occupational health records. We compared 6-month return-to-work rates between workers with one or more comorbid conditions with those without documented comorbidity. Workers with comorbidity were 1.31 times more likely to remain work disabled than those with uncompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 30 publications
3
27
0
2
Order By: Relevance
“…The MUSIC-Norrtä lje material consists of a baseline study, with a case-referent design, performed 1994-1996 and a 5-year follow-up study of the same individuals (n = 2,329) [9,20,26,33].…”
Section: Methodsmentioning
confidence: 99%
“…The MUSIC-Norrtä lje material consists of a baseline study, with a case-referent design, performed 1994-1996 and a 5-year follow-up study of the same individuals (n = 2,329) [9,20,26,33].…”
Section: Methodsmentioning
confidence: 99%
“…Morken et al (29) found that an increase in the number of pain sites increased the risk of SA due to musculoskeletal disorders in a two-year follow-up among industrial workers. In the occupational health setting, the workers with low-back pain and concurrent other musculoskeletal complaints at another site were more likely to remain longer on a sick leave compared to those with only low back pain (30).…”
Section: Haukka Et Almentioning
confidence: 99%
“…Low self-perceived health therefore may be an important obstacle for RTW and should be addressed. Note that selfperceived health cognitively differs from measures of comorbidity because self-perceived health includes a self-evaluation of health, while measures of comorbidity are reports of different symptoms that are also related to outcome [72]. -Noteworthy, it is a strong point that not only expectations and values of patients and supervisors and colleagues are important, but also those of physicians and others.…”
Section: Work-related Expectations and Evaluations That May Become Obmentioning
confidence: 99%